The Effects of Chinese Herbal Decoction Combined with Recombinant Human Interferon α2b on MRI Imaging, Tumor Markers, and Immune Function in Patients with Renal Cell Carcinoma - Siliang Song (Hindawi Limited, 2021)
Background. To explore the clinical efficacy of traditional Chinese medicine decoction combined with recombinant human interferon α2b in the treatment of renal cell carcinoma (RCC). Methods. 68 RCC patients were divided into the control group and treatment group (n = 34). The control group was treated with recombinant human interferon α2b, and the treatment group was treated with traditional Chinese medicine decoction on the basis of the control group. The clinical efficacy and life quality were observed. At the same time, the changes of immune function before and after treatment were compared. Results. After one course of treatment, the effective rate and clinical benefit rate of the treatment group were higher than those of the control group. The Karnofsky score in the treatment group was better than that in the control group. In improving the immune function, the treatment group was better than the control group in increasing CD3+ and CD4+ and reducing CD8+. Conclusion. Traditional Chinese medicine decoction combined with recombinant human interferon α2b has a good effect on the treatment of RCC. It can not only improve the common clinical symptoms of patients but also improve the quality of life and cellular immune function of patients.